Individual modes and patterns of rational and intuitive decision-making by purchasing managers. Issue 2 (March 2017) - Kaufmann, Lutz; Wagner, Claudia M.; Carter, Craig R.
Abstract: This study extends the literature on decision modes in purchasing. While decision modes have traditionally been divided broadly into rational and intuitive processing modes (dual-process approach), following the tenet of recent psychology research, we further differentiate the latter into experience-based and emotional processing (multiple systems approach). Previous decision-making research has been inconsistent in its findings about the relationship between decision modes and performance. Using the purchasing manager's supplier selection decision process as our unit of analysis, we first investigate the relationship between individual decision modes and the financial and non-financial performance of the selected supplier. Hierarchical regression analyses indicate that rational processing is positively related to both financial and non-financial performance, while emotional processing is negatively related to financial performance, and the interaction of rational and emotional processing is positively related to both performance outcomes. Because recent cognitive psychology assumes that some combination of rationality and intuition is commonly used, we then apply a configuration approach and develop a taxonomy of decision-making modes surrounding supplier selection. Cluster analysis results show five decision-making patterns that are related to the performance of the selected supplier. Highlights: Multiple cognitive systems interact. Rational processing is key; intuitive modes play a complementary role. Employs hierarchical regression analysis and an inductive configuration approach. Managers should use multiple decision making modes.